A common functional polymorphism in the promoter region of the microsomal triglyceride transfer protein gene influences plasma LDL levels. - Karpe, F; Lundahl, B; Ehrenborg, E; Eriksson, P; Hamsten, A (1998)
Microsomal triglyceride transfer protein (MTP) is required for the assembly and cellular secretion of apolipoprotein B (apoB) -containing lipoproteins from the liver and intestine. The secretion pattern of apoB-containing lipoproteins is likely to influence the VLDL and LDL levels in plasma. By initial opportunistic screening for polymorphic sites in the regulatory region of the MTP gene by gene sequencing in 20 healthy male subjects, a common functional G/T polymorphism was detected 493 bp upstream from the transcriptional start point. There was differential binding of unique nuclear proteins at this site, as shown by electrophoretic mobility shift assay. The G variant seemed to bind two or three nuclear proteins that do not bind to the T variant. Expression studies with minimal promoter constructs linked to the chloramphenicol acetyltransferase reporter and transfected into HepG2 cells revealed marked enhancement of transcriptional activity with the T variant. The prevalence of the MTP promoter genotypes was investigated in a group of 184 healthy, middle-aged white men; the frequency of homozygosity for the MTP -493 T variant was .06 and the allele frequency of MTP -493T was .25 in the population. These homozygous subjects had a 22% lower LDL cholesterol concentration than did heterozygotes or subjects homozygous for the MTP -493 G variant (2.9+/-0.6 versus 3.7+/-0.8 mmol/L, P<.05). Analysis of apoB and triglyceride contents in VLDL subfractions revealed a markedly changed balance within the VLDL population. Subjects homozygous for the MTP -493 T variant had fewer but more lipid-rich VLDL particles, thereby arguing for an effect of MTP expression on the hepatic secretion of triglyceride-rich, apoB-containing lipoproteins. This common genetic variation of the MTP promoter is likely to have important implications for cardiovascular disease.